Optimizing Teacher Work Productivity through Transformational Leadership, Organizational Climate, and Teamwork - Dedy Yusuf Aditya; Sri Setyaningsih; Griet Helena Laihad (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This study aims to analyze the factors influencing teacher work productivity in elementary schools in Tasikmalaya Regency. The research focuses on transformational leadership, organizational climate, teacher collaboration, and work motivation as variables contributing to teacher productivity. A mixed-methods approach was employed, consisting of two main phases: qualitative and quantitative. The qualitative phase involved in-depth interviews to identify the current conditions of teacher work productivity and dominant influencing factors. The quantitative phase included 163 respondents selected using proportional random sampling, with data analyzed using Partial Least Square (PLS) Structural Equation Modeling (SEM). The findings reveal that transformational leadership and organizational climate have a direct and significant impact on teacher collaboration and work productivity. Teacher collaboration also significantly influences teacher work productivity. However, the indirect effects of transformational leadership and organizational climate on teacher work productivity through collaboration are positive but not significant. This study identifies strategies, methods, and optimal efforts to improve the work productivity of public elementary school teachers in Tasikmalaya Regency. Furthermore, the study provides strategic recommendations based on Sitorem analysis to strengthen transformational leadership, enhance organizational climate, and foster effective collaboration to improve teacher work productivity.